Meningkatkan Kreativitas Peserta Didik dalam Melukis Melalui Teknik Finger Painting pada Pelajaran Seni Budaya - Mia Andini; Euis Eka Pramiarsih; Ludi Herawan (Fakultas Keguruan dan Ilmu Pendidikan Universitas Langlangbuana, 2019)
This research is motivated by several problems in the subject of Arts and Culture, namely the lack of creativity in painting low- grade students. This study aims to determine the increase in painting creativity using Finger Painting Techniques I grade 066 SD Negeri Halimun Bandung. This research is quantitative with the research design Quasi Experiment Design. This study using two-class samples namely, Experimental Class and Control Class with a total of 30 students in each class. The research instrument was in the form of a Practice Test and then the results of the Practice Test were assessed following the creativity indicators and filled in the Teacher's Observation Sheet, the Observation Sheet on the Finger Painting Technique that had been Judged by Expert Lecturers in their fields. The results showed an increase in student creativity in doing the art of painting with the technique of Finger Painting in art and culture subjects in class I and there were differences in the increase in creativity that occurred between the experimental class and the conventional class.